Inhibition of cytochrome P450 enzymes by thymoquinone in human liver microsomes - Ahmed A. Albassam (Saudi Pharmaceutical Journal, 2018)
The aim of the present study was to investigate the potential effect of thymoquinone (TQ) on the metabolic activity of four major drug metabolizing enzymes in human liver microsomes, namely cytochrome P450 (CYP) 1A2, CYP2C9, CYP2D6 and CYP3A4. The inhibition of CYP enzymatic activities by TQ was evaluated by incubating typical substrates (phenacetin for CYP1A2, tolbutamide for CYP2C9, dextromethorphan for CYP2D6, and testosterone for CYP3A4) with human liver microsomes and NADPH in the absence or presence of TQ (1, 10 and 100 µM). The respective metabolite of the substrate that was formed was measured by HPLC. Results of the presented study presented that the metabolic activities of all the investigated CYP enzymes, viz. CYP1A2, CYP2C9, CYP2D6 and CYP3A4, were inhibited by TQ. At 1 µM TQ, CYP2C9 enzyme activity was maximally inhibited by 46.35%, followed by CYP2D6 (20.26%) > CYP1A2 (13.52%) > CYP3A4 (12.82%). However, at 10 µM TQ, CYP2C9 enzyme activity was maximally inhibited by 69.69%, followed by CYP3A4 (23.59%) > CYP1A2 (23.51%) > CYP2D6 (11.42%). At 100 µM TQ, CYP1A2 enzyme activity was maximally inhibited by 81.92%, followed by CYP3A4 (79.24%) > CYP2C9 (69.22%) > CYP2D6 (28.18%). The IC50 (mean ± SE) values for CYP1A2, CYP2C9, CYP2D6 and CYP3A4 inhibition were 26.5 ± 2.9 µM, 0.5 ± 0.4 µM, >500 µM and 25.2 ± 3.1 µM, respectively. These findings suggest that there is a high probability of drug interactions resulting from the co-administration of TQ or herbs containing TQ with drugs that are metabolized by the CYP enzymes, particularly CYP2C9. Keywords: Thymoquinone, Cytochrome P450, Metabolism, Human liver microsomes